Ductility Evaluation of Damaged Recycled Aggregate Concrete Columns Repaired With Carbon Fiber-Reinforced Polymer and Large Rupture Strain FRP - Li, Pengda; Zhao, Yao; Long, Xu; Zhou, Yingwu; Chen, Zhenyuan (Frontiers in Materials, 2020)
Producing recycled aggregates inevitably causes recycled aggregate damage during a crushing process. This inherent defect results in the recycled aggregate concrete feature inferior mechanical properties compared with natural aggregate concrete (NAC), and this drawback also leads to the RAC being rarely adopted in structures. Existing research has shown that the strength and ductility of damaged concrete in compression members can be significantly enhanced through external confinement using fiber-reinforced polymer (FRP) wraps. This application has been widely used in concrete structures repairing and retrofitting technology. However, there is little research on the effects of these existing aggregates damages coupling with different load damage conditions on the mechanical properties of such FRP confined concrete. This paper presents the results of an experimental study on the behavior of pre-damaged recycled aggregate concrete cylinders that was repaired with carbon fiber-reinforced polymer (CFRP) or larger rupture strain (LRS)-FRP jackets. Tests were conducted on 58 concrete columns involving variations of replacement ratio, damage levels, and FRP properties. The test results demonstrated that the ultimate strain and strength of damaged recycled aggregate concrete could be significantly enhanced by wrapping FRP, and the aggregates quality plays a vital role in the strength of confined concrete. Also, the energy absorption of CFRP and LRS-FRP confined RAC were evaluated, and the analysis indicated that compared with CFRP, LRS-FRP can greatly improve the energy absorption capacity of RAC, so that LRS-FRP confined concrete has a good potential to achieve the ductile design of concrete columns, especially for its application in seismic reinforcement.